Investigating neuronal function with optically controllable proteins - Zhou, Xin X.; Pan, Michael; Lin, Michael Z. (Frontiers in Molecular Neuroscience, 2015)
In the nervous system, protein activities are highly regulated in space and time. This regulation allows for fine modulation of neuronal structure and function during development and adaptive responses. For example, neurite extension and synaptogenesis both involve localized and transient activation of cytoskeletal and signaling proteins, allowing changes in microarchitecture to occur rapidly and in a localized manner. To investigate the role of specific protein regulation events in these processes, scientists have been developing tools for optical control of the activity of specific proteins. In this review, we focus on how some recently developed optical control modules have been used in neuroscience applications. These tools have demonstrated impressive versatility in controlling various protein families and thereby cellular functions, and possess enormous potential for future applications in nervous systems. Just as optogenetic control of neuronal firings using rhodopsins has changed how we investigate circuitry function in vivo, optical control may yet yield another revolution in how we study intracellular signaling activities in the brain.